Improving the Ability to Write Expository Texts Through the Four Square Writing Techniques Learning Method and the Use of Picture Card Media - Fika Fransiska; Missriani; Siti Rukiyah (Journal of Practice Learning and Educational Development, 2025)
Study This aiming to: (1) Know implementation method learning four square writing techniques and using card media illustrated in increase ability student Class V of Sembawa 9th State Elementary School write text exposition; (2) Knowing the magnitude improvement ability write text exposition student Class V of Sembawa 9th State Elementary School through implementation method learning four square writing techniques and using card media illustrated. Type of research This is study actions carried out in 2 cycles and each cycle consists of from two meetings with allocation time every 2x35 minute meeting. Research This carried out in class V of SDN 9 Sembawa Regency Banyuasin . Data collection techniques are carried out through writing test activity text exposition. Research results This show that: (1) Through implementation method learning four square writing techniques and using card media illustrated ability student Class V of SDN 9 Sembawa write text exposition can increased; (2) The size percentage improvement ability student Class V of SDN 9 Sembawa write text exposition from implementation test in cycle I to cycle to II is 92.30%.